2018
DOI: 10.15253/2175-6783.2018193254
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de estresse de pais de recém-nascidos em Unidade de Terapia Intensiva Neonatal

Abstract: Objetivo: avaliar níveis de estresse de pais de recém-nascidos em Unidade de Terapia Intensiva Neonatal. Métodos: pesquisa transversal e analítica realizada com 57 pais de recém-nascidos. Foi aplicado questionário de dados sociodemográficos do recém-nascido e dos pais e Parental Stress Scale: Neonatal Intensive Care Unit. Realizou-se análise de frequência, medidas de posição dos escores, teste de Mann-Whitney e teste t-Student. Resultados: no domínio “Alteração no papel de mãe/pai”, a concentração das resposta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
(14 reference statements)
0
3
0
6
Order By: Relevance
“…It was observed that the subscale "Changes in parental roles" presented a moderate general level of stress. A study that investigated the stress levels of 57 fathers and mothers of preterm infants under 37 weeks of age at admission and discharge found a similar trend in maternal stress in their Metric 2 results regarding the "Changes in parental roles" subscale, with moderate general stress levels (8) .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It was observed that the subscale "Changes in parental roles" presented a moderate general level of stress. A study that investigated the stress levels of 57 fathers and mothers of preterm infants under 37 weeks of age at admission and discharge found a similar trend in maternal stress in their Metric 2 results regarding the "Changes in parental roles" subscale, with moderate general stress levels (8) .…”
Section: Discussionmentioning
confidence: 84%
“…Regarding maternal characteristics, the results showed a prevalence of women under 35 years old, mostly single and with no other children. In a previous study, women were also young, but mostly married and with one child (8) . A cross-sectional study that identified sources of stress in mothers and fathers of preterm infants as associated with sociodemographic, obstetric and child characteristics reported that maternal age is not associated with stress levels (5) .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Vários estudos (Holditch-Davis et al, 2015; Wereszczak, Miles, Holditch-Davis, 1997) reconhecem a existência de determinantes que influenciam a forma como os pais experienciam as exigências da parentalidade e alguns investigadores consideram que estes determinantes podem ter origem multifatorial. As fontes de stress, por eles consideradas, estão relacionadas com a perda e/ou alteração do papel maternal, aparência e comportamento do RN, o ambiente da UCN, e as relações com os profissionais de saúde e as respostas exibidas são a ansiedade, desamparo, perda de controlo sobre o que lhes está a acontecer, medo, incerteza e preocupação em relação ao futuro do bebé, culpa, vergonha, depressão, tristeza, desapontamento (Busse et al, 2013;Stübe et al, 2018) . Estudos referem que os pais de RN internados na UCN podem sofrer de Síndrome de Stress Pós-Traumático (SSPT) (Butterfield, 2019;Shaw et al, 2009) (Wereszczak, Miles, Holditch-Davis, 1997).…”
Section: Enquadramento Teóricounclassified
“…INTERAÇÃO EM PSICOLOGIA | vol 24 | n 02 | 2020 A Unidade de Terapia Intensiva Neonatal (UTIN), por ser um ambiente permeado de barulho, equipamentos desconhecidos, rotinas rígidas, muitas pessoas se movimentando constantemente, é considerada uma fonte de estresse (Stübe, Rosa, Pretto, Cruz, Morin & Stumm et al, 2018;Jordão, Pinto, Machado, Costa, & Trajano et al, 2016). Em outros termos, é uma situação que excede a capacidade e recursos financeiros e físicos dos familiares para lidar com as demandas do ambiente e pessoais (Folkman, 2011).…”
unclassified